(untitled) (UBS Scientific Bulletin, 2025)
In the article, the factors that led to the introduction of digitalization processes in agriculture are the global preconditions that caused them: the issue of providing food to the growing population, the unhealthy competitive environment in the industry, the problem of social conservatism and shortage of qualified personnel for innovation, ensuring the proper functioning of supply chains in the process of globalization , the issue of the monopoly of genetically modified seeds and the organization of information was analyzed.